2018
DOI: 10.3390/app8010089
|View full text |Cite
|
Sign up to set email alerts
|

An Ensemble Classifier with Random Projection for Predicting Protein–Protein Interactions Using Sequence and Evolutionary Information

Abstract: Identifying protein-protein interactions (PPIs) is crucial to comprehend various biological processes in cells. Although high-throughput techniques generate many PPI data for various species, they are only a petty minority of the entire PPI network. Furthermore, these approaches are costly and time-consuming and have a high error rate. Therefore, it is necessary to design computational methods for efficiently detecting PPIs. In this study, a random projection ensemble classifier (RPEC) was explored to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 50 publications
0
9
0
1
Order By: Relevance
“…But it seems that (Wang et al, 2017b) obtained the highest performance according to each evaluation metric and the following one is RFEC (Song et al, 2018). Note that, the Legendre moments (LMs) (Wang et al, 2017b), Zernike moments (ZM) descriptor (Wang et al, 2017a) and the evolutionary information (Song et al, 2018) all extracted discriminatory information embedded in the position-specific scoring matrix (PSSM) which is generated by Position-Specific Iterated Basic Local Alignment Search Tool (PSI-BLAST) (Altschul et al, 1997). Above three methods run much slower because it is required to run BLAST against a huge protein NR database to generate a PSSM matrix as its feature.…”
Section: Resultsmentioning
confidence: 99%
“…But it seems that (Wang et al, 2017b) obtained the highest performance according to each evaluation metric and the following one is RFEC (Song et al, 2018). Note that, the Legendre moments (LMs) (Wang et al, 2017b), Zernike moments (ZM) descriptor (Wang et al, 2017a) and the evolutionary information (Song et al, 2018) all extracted discriminatory information embedded in the position-specific scoring matrix (PSSM) which is generated by Position-Specific Iterated Basic Local Alignment Search Tool (PSI-BLAST) (Altschul et al, 1997). Above three methods run much slower because it is required to run BLAST against a huge protein NR database to generate a PSSM matrix as its feature.…”
Section: Resultsmentioning
confidence: 99%
“…In mathematics and statistics, Random Projection (RP) is a classifier for dimensionality reduction of some points which lie in Euclidean space. RP classifier showed that N points in N dimensional space can almost always be mapped to a space of dimension ClogN with command on the ratio of error and distances [46, 47]. It has been successfully applied in rebuilding of frequency-sparse signals [48], face recognition [49], protein subcellular localization [50] and textual and visual information retrieval [51].…”
Section: Materials and Methodologymentioning
confidence: 99%
“…The method was then tested on three databases, using fivefold cross-validation. The accuracies reported ranged from 88 to 97% depending on the dataset used [124].…”
Section: Binding Affinities and Interactionsmentioning
confidence: 99%